Estrategia didáctica basada en la resolución de problemas y el aprendizaje de rectas en cuerpos geométricos en estudiantes de primaria - Castro Zanoni, Milagros Soledad (2020)
The purpose of the present study was to elaborate and apply a strategy based on the resolution of problems in the achievement of learning of parallel and perpendicular lines in geometrical figures in students of third grade of primary level, curricular area of mathematics. For the application of the strategy a learning session was elaborated in which the empirical modeling and systemic methods were applied. In the foundation we worked with the analytical - synthetic, inductive - deductive and comparative theoretical methods. The execution took into account the techniques of the exhibition, the team work, the collaborative work. In the evaluation, the techniques of hetero-evaluation, co-evaluation and self-evaluation were applied. After the conclusion of the session, it was concluded that the students achieved the learning of parallel and perpendicular lines in geometric figures.